Pengaruh Penggunaan Booklet Tanda Bahaya Kehamilan Terhadap Pengetahuan Ibu di Puskesmas Sungai Ambawang Tahun 2025: Anastasia Lina, Anjelina Sera - Anastasia Lina; Anjelina Sera (STIKes Persada Husada Indonesia, 2026)
One educational medium considered effective in improving health knowledge is the booklet. Booklets are printed media that present information concisely and clearly, complemented by visual illustrations, making them easily understood by target groups with varying educational levels. This study aimed to determine the effect of using a pregnancy danger signs booklet on the knowledge level of pregnant women at the Sungai Ambawang Community Health Center in 2025. This study used a quantitative pre-experimental design with a one-group pretest–posttest design. The sample consisted of 32 pregnant women selected using a total sampling technique. The intervention consisted of health education using a pregnancy danger signs booklet, accompanied by a health worker. Knowledge data were collected through a questionnaire that had been tested for validity and reliability, and the data were analyzed using a Paired Sample t-test. There was a significant increase in the level of knowledge of pregnant women after being given the pregnancy danger signs booklet intervention, with a p-value of 0.001 (p < 0.05) and a mean difference of 1.44. It can be concluded that the use of the pregnancy danger signs booklet has a significant impact on increasing maternal knowledge.